Successive statistical analysis of extreme air temperature anomalies - Kovalchuk, L. A. (Reports of the National Academy of Sciences of Ukraine, 2015)
The statistical analysis of daily air temperature anomalies in Kiev from 1900 to 2013 is consistently implemented. By the Wald test, it is revealed that the positive extreme temperature anomalies during the past century were statistically significantly higher than 5.00 °C or below 6.67 °C and negative below the extreme abnormalities –5.00 °C and above –9.50 °C. The increase in the frequency of extreme positive anomalies and the decrease in the frequency of negative air temperature anomalies over the past two decades are found.